Systems and methods for shunt power factor correction - Beebe, Ronald; Eckerson, David; Compton, Christopher; Liu, Yizhe; Talebi-Rafsanjan, Salman (2022)
Systems and methods are disclosed that operate to correct the electrical characteristics of an electric distribution system based on analysis at a particular point in the system, for example, at a customer's meter. To do so, the subject characteristic may be measured at the meter. The subject characteristic may be provided to a power inverter controller, which responds by modifying the characteristic of the inverter output to achieve the desired measurement at the meter.